Urban development and redevelopment in San Francisco. - Godfrey, Brian J. (Geographical Review, 1997)
San Francisco has arisen as an “instant city” not once but three times: after the California Gold Rush (1849–1875), following the 1906 earthquake and fire (1906–1930), and with the modern high-rise city (1960–1985). These pivotal periods of intense city building, each about twenty-five years in duration, have been separated by a generation of relative stability. Current redevelopment activity raises an intriguing historical-geographical question: Is a fourth instant city in the making? Reprinted by permission of the publisher.